Exploring the influence that the Pick N Pay online shopping platform has on the purchase behaviour of Generation X and the impact this has on brand perception. - Mlunjwana, Paloma (The IIE, 2020)
Over the years, consumers have been buying items from traditional retail stores. With the emergence of online shopping platforms, there is a high chance that consumers will never have to leave their homes to purchase goods and services. Furthermore, the fact that it is easier to open an online business than a traditional store helps in the growth rate of e-commerce, where consumers can shop online from a wide range of products. In this context, the study explored the influence of the Pick N Pay online shopping platform on Generation X's shopping behavior and its impact on brand perception. The study used a qualitative approach involving thematic and content analysis to achieve the research objectives. Economy is one of the factors that has been found to have a substantial influence on purchasing behavior from the online platform. While a significant percentage said online shopping is cheaper and simpler, some proportions argued that traditional shopping is more convenient due to charges such as shipping costs and the inability to manage online accounts.
Keywords: e-commerce; Online business; Retail industry; Customer behaviour; Consumer Behaviour Theory